Foundational convictions, ethical instruction and theologising in Paul - Jaquette, J. L. (1995)
Recent studies have demonstrated an appreciation of Paul's appropriation and adaptation of popular moral traditions and have addressed the question of influence by exploring the subtle and nuanced contours of the apostle's moral teaching. This study shows (1) how a venerable Jewish symbol (election) provides the convictional framework within which appropriate behaviour is defined, (2) how Paul adapts a common Hellenistic philosophical topos (the Greco-Roman eudaimonists' distinction between important matters and irrelevant ones : the adiaphora - for use in a different symbolic universe, and (3) how the apostle uses the diverse traditions he inherits as words targeted for different exigencies.
Keywords: Ethics; Election; Theology; Paul; Christianity